Effect of corticosteroid and immune-suppressive drugs on oral manifestations in hospitalized COVID-19 patients - Ahmed Mohamed Al Elgendy; Enas Ahmed Elgendy; Marwa Sabry; Mohamed Kamal Salama; Tamer Aboshady (Journal of the Pakistan Medical Association, 2023)
Objective: To explore if the oral lesions in coronavirus disease-2019 patients are caused by the drugs used in the treatment or by the virus itself. Method: The cross-sectional study was conducted from September 2020 to September 2021 at the Kafrelsheikh University Hospital, Egypt, and comprised coronavirus disease-2019 patients of either gender aged 20-60 years having severe pneumonia and breathing difficulties who had no comorbidities. Based on the level of interleukin-6 and procalcitonin, the patients were classified into high group I receiving tocilizumab and methylprednisolone, medium group II receiving methylprednisolone alone, and low group III receiving antiviral drugs. The oral manifestations were recorded at the time of admission before treatment and at 2 weeks after the respective treatment. Data was analysed using SPSS 20. Results: Of the 90 patients, 30(33.3%) were in group I; 16(%) males and 14(%) females with mean age 44.82±6.10 years. Group II had 27(%) patients; 14(%) males and 13(%) females with mean age 43.74±4.87 years. Group III had 33(%) patients; 9(%) males and 14(%) females with mean age 42.66±2.51 years (p>0.05). There was no significant difference among the groups at baseline and after 2 weeks of treatment regarding oral manifestations. Intragroup comparison demonstrated a significant difference in the two values in all the three groups (p<0.05). Conclusion: Oral lesions in coronavirus disease-2019 patients were caused by the virus itself rather than the drugs used in its treatment. Keywords: Tocilizumab, Dentists, Methylprednisolone, COVID-19.